Altered Neural Reactivity in Adolescents With Nonsuicidal Self-Injury During Exposure to Self-Injury Related Cues: Electrophysiological Evidence From a Two-Choice Oddball Paradigm - Zhou, Dong-Dong; Zhao, Lin; Ma, Ling-Li; Hu, Jin-Hui; Chen, Ran; Jiang, Zheng-Hao; He, Xiao-Qing; Peng, Xin-Yu; Liu, Xin-Yi; Li, Xiao; Chen, Wan-Jun; Wang, Wo; et al. (Frontiers in Psychiatry, 2022)
Background Nonsuicidal self-injury (NSSI) may be a type of addiction, that is characterized by cue reactivity. We aimed to explore the behavioral performance and neural reactivity during exposure to self-injury cues in adolescents with NSSI and major depressive disorder (MDD). Methods Eighteen MDD patients, 18 MDD patients with NSSI, and 19 healthy controls (HC) were recruited to perform a two-choice oddball paradigm. All subjects were 12–18 years old. Neutral cues and self-injury related cues separately served as deviant stimuli. Difference waves in N2 and P3 (N2d and P3d) were derived from deviant waves minus standard waves. Accuracy cost and reaction time (RT) cost were used as behavioral indexes, while the N2d and P3d were used as electrophysiological indexes; the N2d reflects early conflict detection, and the P3d reflects the process of response inhibition. Results No significant main effects of group or cue or an effect of their interaction were observed on accuracy cost and P3d latency. For RT cost, N2d amplitude, and N2d latency, there was a significant main effect of cue. For P3d amplitude, there was a significant main effect of cue and a significant group × cue interaction. In the NSSI group, the P3d amplitude with self-injury cues was significantly larger than that with neutral cues. However, there was no such effect in the MDD and HC groups. Conclusions Adolescents with NSSI showed altered neural reactivity during exposure to self-injury cue. Further studies with larger sample sizes are needed to confirm our results.